The Effect of Narrative on Physical Activity via Immersion During Active Video Game Play in Children: Mediation Analysis - Sousa, Caio Victor; Fernandez, Austin; Hwang, Jungyun; Lu, Amy Shirong (JMIR Publications, 2020)
BackgroundActive video games (AVGs) can increase physical activity (PA) and help produce higher physiological expenditure. Animated narrative videos (NVs) possess unique immersive and motivational properties. When added to AVGs, they have been found to increase moderate-to-vigorous physical activity (MVPA) as opposed to the original no video condition. However, there is no evidence of whether that was due to the NV or the addition of an animated video to an AVG. ObjectiveThis study aimed to investigate the differential effect of adding an NV versus a nonnarrative video (NNV) to an AVG on PA parameters and physiological responses and to explore the mediating role of immersion. MethodsA total of 22 children aged 8 to 12 years were randomly assigned to the NV or NNV condition. They were instructed to play an AVG (on Xbox Kinect) for as long as they wanted. We used accelerometers to estimate the time spent (in minutes) in MVPA. Heart rate (HR) and rate of perceived exertion (RPE) were measured before, during, and after the AVG play session. The participants then reported their experience of narrative immersion via a questionnaire. ResultsThe NV group had significantly higher narrative immersion (mean 3.50, SD 0.55 vs mean 2.91, SD 0.59; P=.03) and MVPA (mean 19.46, SD 13.31 vs mean 7.85, SD 5.83; P=.02) than the NNV group. Narrative immersion was positively correlated with MVPA (r=0.52; P=.01) and average HR during AVG (r=0.43; P=.05). Mediation analysis indicated that narrative immersion mediated the effect of NV (NV vs NNV) on MVPA (direct effect: beta=7.51; P=.01). The indirect effect was that NV was positively correlated with the mediator variable narrative immersion (beta=.59; P=.03), which was itself marginally associated with MVPA (beta=6.95; P=.09); when narrative immersion was included in the model, the regression coefficient was attenuated. ConclusionsAVG with added narratives elicits more narrative immersion, resulting in more minutes in MVPA. Narrative immersion served as a mediator between NV and MVPA via its elicitation of an elevated HR without increasing RPE. The inclusion of immersive narratives in AVG could be helpful for inducing MVPA, to enhance AVG engagement without additional exertion.